2020
DOI: 10.1111/dme.14223
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DAFNE education, continuous subcutaneous insulin infusion, or both in a population with type 1 diabetes in Scotland

Abstract: Aim To investigate the effect of DAFNE and continuous subcutaneous insulin infusion in clinical practice.Methods Within NHS Lothian, continuous subcutaneous insulin infusion started in 2004 and DAFNE education began in 2006. We extracted anonymized data from the national database for all those aged > 18 years with type 1 diabetes having a Dose Adjustment For Normal Eating course or continuous subcutaneous insulin infusion start date (n = 4617). ResultsIn total, 956 persons received DAFNE education, and 505 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…Other factors, such as persistent C‐peptide secretion, 11,12,16 male gender, 17 lower BMI 18,19 and non‐ smoking status, 18 have been reported but their relationship to HbA 1c in type 1 diabetes has not been consistently demonstrated, particularly independently of potential confounders. Participation in DAFNE was not independently associated with meeting glycaemic targets, although our centre has previously demonstrated that completing DAFNE is prospectively associated with substantial improvement in HbA 1c 6 …”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Other factors, such as persistent C‐peptide secretion, 11,12,16 male gender, 17 lower BMI 18,19 and non‐ smoking status, 18 have been reported but their relationship to HbA 1c in type 1 diabetes has not been consistently demonstrated, particularly independently of potential confounders. Participation in DAFNE was not independently associated with meeting glycaemic targets, although our centre has previously demonstrated that completing DAFNE is prospectively associated with substantial improvement in HbA 1c 6 …”
Section: Discussionmentioning
confidence: 73%
“…We have shown that a range of factors are independently associated with the likelihood of having an HbA 1c below the national target for people with type 1 diabetes. Some factors, such as flash monitoring use, 8,14 CSII use 6,7 and lower socioeconomic deprivation, 15 would be fully expected based on previously published data. Other factors, such as persistent C‐peptide secretion, 11,12,16 male gender, 17 lower BMI 18,19 and non‐ smoking status, 18 have been reported but their relationship to HbA 1c in type 1 diabetes has not been consistently demonstrated, particularly independently of potential confounders.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…CSII therapy initiation in Scotland follows criteria set by the National Institute for Health and Care Excellence (NICE) guidelines [ 6 ], Scottish Government policy and individual National Health Service (NHS) health board budget allocation decisions. A recent study [ 7 ] examined the effect of CSII therapy on HbA 1c among people with type 1 diabetes in the Scottish health board Lothian and found a significant decrease in HbA 1c following CSII initiation, particularly among those with suboptimal glycaemic control. In this paper, we widen the scope of that analysis by focusing on CSII therapy initiation in people with type 1 diabetes throughout Scotland.…”
Section: Introductionmentioning
confidence: 99%